Hypoglycaemic activity of Bauhinia holophylla through GSK3-β inhibition and glycogenesis activation - Nathalia Ap. De Paula Camaforte; Luiz Leonardo Saldanha; Priscilla Maria Ponce Vareda; João M. Rezende-Neto; Mario R. Senger; Aislan Q. Delgado; Henrique J. N. Morgan; Natalia Moretti Violato; Laís Goyos Pieroni; Anne Lígia Dokkedal; Floriano P. Silva-Júnior; José Roberto Bosqueiro (Taylor & Francis Group, 2019)
Context: Bauhinia L. species, including Bauhinia holophylla (Bong.) Steud. (Fabaceae), have traditionally been used to treat diabetes. Bauhinia is a complex botanical genus, and the indiscriminate use of the diverse Bauhinia species is reflected in the experimental divergence of their medicinal potential. Objective: The hypoglycaemic and hypolipidaemic effects, molecular mechanism of action and phytochemical properties of an authentic extract of B. holophylla leaves were evaluated. Materials and methods: A phytochemical study of a 70% EtOH extract was performed using FIA-ESI-IT-MS/MSn and HPLC-PAD-ESI-IT-MS. The extract (200 or 400 mg/kg b.w.) was administered for 14 days to streptozotocin-induced diabetic Swiss mice. Glucose tolerance and insulin sensitivity, blood parameters, gene and protein expression, and the in vivo and in vitro inhibition of intestinal glucosidases were assessed. Results: HPLC-PAD-ESI-IT-MS analysis identified flavonoid derivatives of quercetin, myricetin, luteolin and kaempferol. Treatment with 400 mg/kg of the extract reduced blood glucose (269.0 ± 32.4 mg/dL vs. 468.0 ± 32.2 mg/dL for diabetic animals), improved glucose tolerance, decreased cholesterol and triglyceride levels, and increased the mRNA expression of proteins involved in glucogenesis in the liver and muscle, such as PI3-K/Akt, GS, GSK3-β (ser-9), AMPK and Glut4. The activity of intestinal maltase was inhibited in vitro (IC50: 43.0 µg/mL for the extract compared to 516.4 µg/mL for acarbose) and in vivo. Discussion and conclusions: Treatment with B. holophylla was associated with a marked hypoglycaemic effect through the stimulation of glycogenesis and inhibition of gluconeogenesis and intestinal glucose absorption, without increasing basal insulinaemia.